Menanamkan Nilai Gotong Royong melalui Kearifan Lokal Desa Penglipuran - Lukman Maulana; Nana Mardian; Rahmita Galuh; Vania Hayunanda (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Gotong royong is a cultural value deeply embedded in Indonesian society, especially in Penglipuran Village, Bali. This village preserves local wisdom that prioritizes togetherness and cooperation in various aspects of life. This study aims to analyze the implementation of gotong royong values in the daily lives of Penglipuran residents and how these values are taught to younger generations. Using a qualitative method with in-depth interviews, the findings reveal that gotong royong is practiced in environmental cleanliness, traditional ceremonies, and other social activities. These values are passed down through informal education within families and project-based activities in schools. Despite the lack of financial support from the government, the community maintains the spirit of gotong royong through social sanctions for those who do not participate. This study highlights how local wisdom can serve as an effective medium for instilling the values of gotong royong in younger generations.